Does Islamic Microfinance indeed base on Sharia-compliant? The Shreds of Evidence Report in Ogan Komering Ilir regency, South Sumatera, Indonesia - Misbahul Munir; Resa Arifatul Arifah; Kharisma Dewi (Universitas Muhammadiyah Yogyakarta, 2021)
The development of Islamic economics and finance in Indonesia in the last few decades has experienced significant developments. It can be seen in the increasing number of sharia businesses in various sectors. From financial institutions, both bank and non-bank financial institutions, Islamic capital markets, sharia bonds (Sukuk) to tourism development managed in a sharia manner. Over time, this rapid development must also be balanced with compliance with sharia values. This study aims to assess Islamic microfinance institutions (BMT) in implementing sharia principles in their products. The product studied in this study is Murabahah. This research uses a qualitative approach with field studies. The results of this study, the BMT studied in this study in general, have implemented sharia values. The implication of this research is to strengthen the compliance of Islamic financial institutions in implementing Islamic values. This research can also be used as a reference by related parties, especially in developing Islamic financial institutions.